Solar System Realms: Stars Taking Up Space Where Planets Could Be - Henry, Todd J.; Paredes, Leonardo A.; Vrijmoet, Eliot; Couperus, Andrew C.; James, Hodari-Sadiki; Jao, Wei-Chun; Kar, Aman; Lesley, DeAndre X.; Casetti-Dinescu, Dana I.; Horch, Elliott P.; Winters, Jennifer G. (2021)
The RECONS (REsearch Consortium On Nearby Stars, www.recons.org) team continues to explore the solar neighborhood by evaluating the nearest stars, both individually and as a population. Key points are becoming clear: we now know that 86% of all stars are K and M dwarfs, and we need to reach to 50 pc and 25 pc, respectively, to create samples of 5000 and 3000 primaries each. These two sizable samples allow us to understand the outcome of the star formation process across a factor of ten in mass as never before. Here we focus on one crucial area of research — stellar companions — with results of our surveys combining radial velocities, astrometry, high-resolution imaging, and trawls of catalogs and the literature. The surveys are carried out primarily at the CTIO/SMARTS 0.9m and 1.5m, the SOAR 4.1m, and both Gemini 8.1m telescopes. We reveal companions at separations from less than 1 AU to more than 1000 AU from the K and M dwarfs, with the key result that these stellar partners are found most often at separations similar to our Solar System. Thus, the star and planet formation processes work on the same spatial scales ... a fact that we must keep in mind as our solar neighborhood becomes enriched with planetary discoveries at distances comparable to where stellar companions are found. This work has been supported by NSF grants AST-0507711, AST-0908402, AST-1109445, AST-1411206, and AST-1715551, AST-1910130, and the SMARTS Consortium.
Conference Name: The 20.5th Cambridge Workshop on Cool Stars, Stellar Systems, and the Sun (CS20.5) Pages: 183 ADS Bibcode: 2021csss.confE.183H
Keywords: K dwarf stars (876) M dwarf stars (982) Multiple stars (1081) Stellar populations (1622); dept.phy